2005
DOI: 10.1021/ja054129q
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Basis of DNA Sugar−Phosphate Cleavage by Low-Energy Electrons

Abstract: DNA damage by low-energy electrons (LEE) was examined using a novel system in which thin solid films of oligonucleotide tetramers (CGTA and GCAT) were irradiated with monoenergetic electrons (10 eV) under ultrahigh vacuum. The products of irradiation were examined by HPLC. These analyses permitted the quantitation of 16 nonmodified nucleobase, nucleoside, and nucleotide fragments of each tetramer resulting from the cleavage of phosphodiester and N-glycosidic bonds. The distribution of nonmodified products sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
176
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(185 citation statements)
references
References 35 publications
8
176
1
Order By: Relevance
“…Thus, these results demonstrate that cleavage of the phosphodiester bond by 4-15 eV electrons takes place via the formation of a sugar radical and a phosphate anion, as also demonstrated in the analysis of the products obtained from DNA bombardment with 10 eV electrons [6]. By using an X-ray secondary electron emission source, Cai et al [28] were able to directly compare DNA damage induced by high energy photons and LEEs under identical experimental conditions.…”
Section: Dna Damage Induced By Low Energy Electronsmentioning
confidence: 53%
See 3 more Smart Citations
“…Thus, these results demonstrate that cleavage of the phosphodiester bond by 4-15 eV electrons takes place via the formation of a sugar radical and a phosphate anion, as also demonstrated in the analysis of the products obtained from DNA bombardment with 10 eV electrons [6]. By using an X-ray secondary electron emission source, Cai et al [28] were able to directly compare DNA damage induced by high energy photons and LEEs under identical experimental conditions.…”
Section: Dna Damage Induced By Low Energy Electronsmentioning
confidence: 53%
“…6 [26]. The probability of strand breaks at different sites along the backbone of GCAT is strongly dependent on site and electron energy [6,15,26,27], indicating that the nature and position of the base play a role in DNA damage, which seems to be an indirect evidence confirming that electron transfer from a base to phosphate is responsible for the SSBs formation. Furthermore, direct electron attachment to the phosphate groups should produce equal amounts of fragments for equivalent bonds.…”
Section: Dna Damage Induced By Low Energy Electronsmentioning
confidence: 92%
See 2 more Smart Citations
“…Li et al 50,51 and Gu and co-workers [52][53][54][55][56][57][58][59] have carried out related electronic-structure studies of nucleoside ͑base+ sugar͒ and nucleotide ͑nucleoside + phosphate͒ neutrals, anions, and radicals with a view of elucidating the energetics of electron attachment and of cleaving both the phosphodiester C-O bonds of the backbone and the N-glycosidic base-sugar bonds. Condensedphase experiments on thymidine and a single-strand oligonucleotide have demonstrated that slow electrons do indeed break the C-O phosphate-sugar bonds as well as the C-N base-sugar bonds, [60][61][62] and C-O bond breaking was also found in gas-phase DA to a model phosphodiester. 63 A few electron-collision studies, experimental and theoretical, have looked at the individual backbone constituents, i.e., ribose or deoxyribose and a phosphate group, [64][65][66][67][68][69] and others have also been made of electron collisions with backbone analogs such as tetrahydrofuran, 29,65,[68][69][70][71][72][73][74][75][76][77][78][79] tetrahydrofurfuryl alcohol, 71,72,80,81 fructose, 79 and dibutyl phosphate.…”
Section: Introductionmentioning
confidence: 97%